15 Years of Progress on Transition Metal-Based Electrocatalysts for Microbial Electrochemical Hydrogen Production: From Nanoscale Design to Macroscale Application - Parsa, Seyed Masoud; Chen, Zhijie; Ngo, Huu Hao; Wei, Wei; Zhang, Xinbo; Liu, Ying; Ni, Bing‑Jie; Guo, Wenshan (Nano-Micro Letters, 2025)
Designing high-performance electrocatalysts is one of the key challenges in the development of microbial electrochemical hydrogen production. Transition metal-based (TM-based) electrocatalysts are introduced as an astonishing alternative for future catalysts by addressing several disadvantages, like the high cost and low performance of noble metal and metal-free electrocatalysts, respectively. In this critical review, a comprehensive analysis of the major development of all families of TM-based catalysts from the beginning development of microbial electrolysis cells in the last 15 years is presented. Importantly, pivotal design parameters such as selecting efficient synthesis methods based on the type of material, main criteria during each synthesizing method, and the pros and cons of various procedures are highlighted and compared. Moreover, procedures for tuning and tailoring the structures, advanced strategies to promote active sites, and the potential for implementing novel unexplored TM-based hybrid structures suggested. Furthermore, consideration for large-scale application of TM-based catalysts for future mass production, including life cycle assessment, cost assessment, economic analysis, and recently pilot-scale studies were highlighted. Of great importance, the potential of utilizing artificial intelligence and advanced computational methods such as active learning, microkinetic modeling, and physics-informed machine learning in designing high-performance electrodes in successful practices was elucidated. Finally, a conceptual framework for future studies and remaining challenges on different aspects of TM-based electrocatalysts in microbial electrolysis cells is proposed. Highlights: 1 Comprehensive overview of the evolution of transition metal-based catalysts in microbial electrolysis cells from their inception to the present. 2 Critical design parameters of catalysts evaluated from technical, economic, and sustainability perspectives. 3 A conceptual framework is proposed to address current challenges and guide future research based on literature best practices.